Cracking and Photo-Oxidation of Polyoxymethylene Degraded in Terrestrial and Simulated Marine Environments - Tang, Chih-Cheng; Chen, Ying-Ting; Zhang, Yi-Ming; Chen, Huey-Ing; Brimblecombe, Peter; Lee, Chon-Lin (Frontiers in Marine Science, 2022)
Marine plastic debris is an environmental problem, and its degradation into microplastics (1-5000 μm) introduces them into the food chain. In this study, small polyoxymethylene (global production 3000 Tg per year) pellets were exposed in terrestrial and simulated marine environments to heat and light, resulting in cracking during decay with increasing IR absorption (OH-bonds). Furthermore, sunlight over three years reduced pellet mass and diameter ( 10% and 40%), initially yielding 100-300 μm fragments. Changes under UV irradiation were smaller as it could not penetrate into particle interiors. Characteristic spacing of surface striations (100-300 µm) initiated radial cracks to pellet interiors, and breakdown ultimately meant 95% of particles were <300 µm, which are potentially incorporated in marine turbidites.